(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The perfect material is difficult to create. If at all possible. Each of the existing ones has its own advantages and disadvantages. But with skillful use, you can mix the shortcomings, and the advantages are fully beneficial. Brick is the oldest building material that is still popular worldwide. At the beginning of the 19th century, bricks were made of burnt clay - first in wood, then coal, and today they are produced in gas furnaces. However, until now, the Hoffmann coal ring furnace - one of the oldest brick manufacturers, Wienerberger - burns hand-molded facing bricks. By the way, the approach is the same as 108 years ago.